An Analysis Influencer Role And Consumer Psychology On Digital Marketing Towards Motives To Buy Millennial Generation’s - Sapto Hadi Imambachri; Desilia Purnama Dewi; Ratna Suminar (European Exploratory Scientific Journal, 2021)
The existence of a large market in Indonesia, of course, invites many companies to compete to offer products and services, so that competition increases sharply and marketers compete to offer their products and good services. For companies and products to get great attention from consumers, the use of influencers is commonplace. It continues to grow so that continuous delivery of messages to consumers through influencers can enter the minds of consumers or is called an awareness area. If one day consumers need the product, then the source of the first information used is the awareness area. If the message is repeated to consumers, what happens is that the message will be stored as the main reference or so-called evoked set, where the main choice by the consumer is in this area. The message can also be stored in the inert set as a second choice for the desired product. The third is in the form of negative messages or products that are avoided to buy, which are called inept sets. This research aims to find out the influencer role in digital marketing towards the millennial generation’s buying motives, to find out the role of consumer psychology in digital marketing towards the millennial generation’s buying motives, and to find out the influencer role and consumer psychology in digital marketing towards motives to buy millennial generation. This research is a type of causality and uses a quantitative approach. The final sample involved 250 respondents. This research assesses motives to buy the millennial generation’s use a statistical inferential, i.e., multiple regression linear analysis. The following tests are obtained: (1) Influencer Role has a positive and a significant influence, and Consumer Psychology is also has a significant influence on the Motives to Buy Millennial Generation. The contribution of Motives to Buy Millennial Generation’s is affected by Influencer Role and Consumer Psychology factors by 66.2 percent.